Sustainable community forest management in West Kalimantan: A case study of the Dayak Katab Kebahan community - Tien Aminatun; Kuswarsantyo; Suhartini; Rangpan, Vichit; Prasojo, Zaenuddin Hudi; Andreyani, Anggun (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2022)
West Kalimantan has great potential of forests and indigenous people. Therefore, it is crucial to study on forest management by indigenous people. The study is aimed at analyzing the forest management carried out by the Dayak Katab Kebahan community; and the condition of the forest ecosystem. The research area is in Melawi Regency, West Kalimantan. Observations and in-depth interviews were conducted to explore the customs in managing forests. A vegetation survey using purposive sampling was performed. The fauna study was conducted by the exploration method. Vegetation data analysis was carried out by calculating the importance value and diversity indices. One-way ANOVA analysis was done to determine the presence of forest ecosystem differences between two forests. The findings showed forest managed by the Dayak Katab Kebahan community has a core zone which is a zone that should not be disturbed, and a cultivation zone which can be utilized and can be intercropped with plantation crops; and the forest ecosystem managed by the Dayak Katab Kebahan community has a higher fauna richness, vegetation diversity index and the importance value index of each species. It is suggested that the government be involved in supporting the customary law of local communities in forest conservation.